The Rare Sugar Tagatose Differentially Inhibits the Growth of Phytophthora infestans and Phytophthora cinnamomi by Interfering With Mitochondrial Processes - Abdessalem Chahed; Abdessalem Chahed; Abdessalem Chahed; Andrea Nesler; Andrea Nesler; Lorella Navazio; Lorella Navazio; Barbara Baldan; Barbara Baldan; Isabella Busato; Isabella Busato; Essaid Ait Barka; et al. (Frontiers in Microbiology, 2020)
Rare sugars are monosaccharides with limited availability in nature and their biological functions are largely unknown. Among them, tagatose was developed as a low-calorie sweetener and showed beneficial effects on human health. Tagatose is metabolized by only certain microbial taxa and inhibits the growth of important crop pathogens (e.g., Phytophthora infestans), but its mode of action and the microbial responses are unknown. The aim of this study was to understand the tagatose mode of action against Phytophthora spp., with the final aim of developing new plant protection products. Tagatose inhibited P. infestans growth in vitro and caused severe ultrastructural alterations, with the formation of circular and concentric mitochondrial cristae. Decreased ATP content and reduced oxygen consumption rate (OCR) were found in tagatose-incubated P. infestans as compared to the control, with the consequent accumulation of reactive oxygen species (ROS) and induction of genes related to apoptosis and oxidative stress response. On the other hand, tagatose did not, or only slightly, affect the growth, cellular ultrastructure and mitochondrial processes in Phytophthora cinnamomi, indicating a species-specific response to this rare sugar. The mode of action of tagatose against P. infestans was mainly based on the inhibition of mitochondrial processes and this rare sugar seems to be a promising active substance for the further development of eco-friendly fungicides, thanks to its anti-nutritional properties on some phytopathogens and low risk for human health.